Institute of Metals Division - Bending of Molybdenum Single Crystals - K. T. Aust; R. Maddin; N. K. Chen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1954)
Lattice rotations occurring on the tension and compression sides during the bending of molybdenum single crystals at room temperature were followed in detail. Observations were also made concerning crystallite rotations and slip traces. 'The results indicated the participation of (110) as slip planes and the<111>as slip directions. Crystallite fragmentation during bending was also noted. EVERAL investigations have been conducted on pure bending of face-centered cubic metals.'-" Structural changes as a result of "bend-gliding," and the importance of bending and constraints during conditions of axial stressing, have been noted.'," It was evident that the mechanism by which the bending deformation occurs is more complex than the case of simple shear. Studies of the bending of body-centered cubic metals from the aspect of the crystallographic mechanism appear to be lacking. Molybdenum single crystals therefore were subjected to deformation by bending in order to determine the reaction of the body-centered cubic lattice to bending stresses. It might be expected for the bending of single crystals that lattice rotation as represented by the axis of compression would proceed toward the pole of the active slip plane and that rotation of the tensile stress axis should indicate the slip direction.' It was believed therefore that a study of the tension and compression sides of bent molybdenum single crystals should give data concerning the operative slip system. Specific problems which are pertinent to the overall picture of plastic deformation were also investigated, e.g., whether the constraints offered by pure bending give rise to the deformation band, and also the nature of the asterism occurring on the tension and compression sides during the stages of deformation. Experimental Procedure Eight single crystal specimens were grown from sintered molybdenum rods 143 in. diameter using the method described previously.6 The purity of this material was reported as 99.9 pct as described elsewhere.' The specimens were % to 1/10 in. in diameter x 7 in. long, with single crystals approximately 1 to 2 in. in length occupying the entire center sections of each specimen. The specimens were elec-trolytically polished using an electrolyte of 300 cc methyl alcohol, 60 cc H2SO4, 130 cc HCl, and a current density of 4 amp per sq in. Each specimen was then loaded in a bending apparatus similar to that used by Yen and Hibbard,' as shown in Fig. 1. The load was applied by means of a spring and screw arrangement through four ball-bearing surfaces set 1.5 in. apart. Either the inner two bearings or the outer two (A, B, Fig. 1) were attached to a movable steel plate (D) through which the load was transmitted. Since the apparatus was mounted on a track of the X-ray apparatus, the tension or compression side of the specimen could